ANALISIS PERTIMBANGAN HAKIM DENGAN DALIL SILENT AGREEMENT PADA PEMUTUSAN HUBUNGAN KERJA (STUDI KASUS PUTUSAN NOMOR : 274/Pdt.Sus-PHI/2020/PN.Bdg.) - Kusyanto; Lenny Nadriana (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Unilateral termination of employment is a condition that is very detrimental to workers. Especially if the compensation for the termination is not in accordance with existing laws and ignores the agreements that have been made, it can cause suffering for the workers affected by the termination. The case of termination of employment against workers with fixed-term contracts (PKWT) in case number 274/Pdt.Sus-PHI/2020/PN.Bdg. is an example illustrating a termination that neglects the legal principles such as the principle of pacta sunt servanda in an employment agreement. The researcher also conducted an analysis of the judge's considerations arguing for the silent agreement by the worker to the unilateral termination carried out by the employer. The research was conducted using a normative legal analysis method with a statuta approach. The researchers compared the judges' considerations with existing laws, books, websites, and legal journals related to the case.